A self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, its preparation method and application

CN122901276APending Publication Date: 2026-10-13JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611207953.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,传统光电化学传感器多采用三电极体系并需外加偏压,增加了系统能耗和复杂性,不利于便携化应用

Benefits of technology

1、构建了双光电极自供能体系,利用Au NPs/g-C3N4光阳极和Ni掺杂ZnIn2S4光阴极的费米能级差形成内建电场,无需外加偏压即可实现自供能检测,简化装置,降低干扰;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122901276A_ABST
    Figure CN122901276A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photoelectrochemical sensors, and particularly relates to a self-powered ZnIn2S4 / g-C3N4 double-electrode photoelectrochemical sensor and a preparation method and application thereof. The sensor uses gold nanoparticle modified graphite phase carbon nitride as a photoanode, uses nickel doped zinc indium sulfide as a photocathode, and fixes mercapto modified omethoate aptamer on the surface of the photoanode through Au-S bonds. The built-in electric field formed between the double photoelectrodes by Fermi level difference can realize self-powered photoelectric signal output under visible light irradiation without an external bias. Based on the interface steric hindrance and charge transfer changes caused by the specific binding of aptamer and omethoate, the photoelectric current signal has a concentration dependent response, so that high sensitive quantitative detection of omethoate is realized. The linear detection range of the sensor for omethoate is 0.001-1000 ng / mL, and the detection limit is as low as 2.75 pM.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photoelectrochemical sensor technology, specifically relating to a self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, its preparation method, and its application. Background Technology

[0002] Omethoate is a highly toxic organophosphate insecticide with strong systemic activity and a broad insecticidal spectrum, and is widely used in agricultural production. However, improper application can easily lead to omethoate residues in agricultural products, soil, and water bodies, which can migrate and accumulate through the food chain, inhibiting the activity of human acetylcholinesterase and posing potential harm to the nervous system. Therefore, establishing a rapid, sensitive, and reliable method for detecting omethoate residues is of great significance for ensuring food safety and the ecological environment.

[0003] In related technologies, the detection of omethoate mainly relies on instrumental analysis methods such as high-performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS). These methods are highly accurate, but the equipment is expensive, the pretreatment is complex, and they require professional personnel to operate, making it difficult to meet the needs of rapid on-site detection. Photoelectrochemical sensing technology has advantages such as low background noise and high sensitivity due to the separation of excitation light and detection electrical signals. However, traditional photoelectrochemical sensors often use a three-electrode system and require an external bias voltage, which increases system energy consumption and complexity, hindering portable applications.

[0004] Therefore, there is an urgent need to design a self-powered dual-photoelectrode photoelectrochemical sensor and its preparation method, its application in the detection of organophosphorus pesticide omethoate, and its detection method, in order to solve the technical problems of the above-mentioned high performance liquid chromatography and gas chromatography-mass spectrometry analysis methods, which are expensive and have complex pretreatment, making it difficult to meet the needs of rapid on-site detection. Photoelectrochemical sensing technology requires an external bias voltage, and the system has high energy consumption and complexity, which is not conducive to portable applications. Summary of the Invention

[0005] This disclosure provides at least one embodiment of the present invention, which belongs to the field of photoelectrochemical sensor technology, specifically relating to a self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, its preparation method, and its application.

[0006] In a first aspect, embodiments of this disclosure provide a self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, comprising: an Au NPs / g-C3N4 photoanode and a Ni-doped ZnIn2S4 photocathode; The surface of the photoanode is fixed with an oxymethol aptamer; The Au NPs / g-C3N4 is a composite material with gold nanoparticles loaded on the surface of tubular graphitic carbon nitride, and the Ni-doped ZnIn2S4 is nickel ion-doped indium zinc sulfide.

[0007] In one optional embodiment, the nucleotide sequence of the oxymethol aptamer is: 5′-Thiol-C6-AAGCTTTTTTGACTGACTGCAGCGATTCTTGATCGCCACGGTCTGGAAAAAGAG-3′.

[0008] Secondly, this disclosure also provides a method for preparing a self-powered dual-photoelectrode photoelectrochemical sensor, applicable to the preparation of the self-powered dual-photoelectrode photoelectrochemical sensor as described above, comprising the following steps: Step S1, Preparation of tubular g-C3N4: Melamine is dissolved in ethylene glycol, and nitric acid aqueous solution is added to form a gel. After filtration, washing, and drying, the gel is calcined in an air atmosphere to obtain tubular g-C3N4. Step S2, preparation of Au NPs / g-C3N4: tubular g-C3N4 is dispersed in methanol-water solution, chloroauric acid solution is added, and after adsorption by stirring in the dark, gold nanoparticles are deposited by light reduction to obtain Au NPs / g-C3N4 composite material. Step S3, Preparation of Ni-doped ZnIn2S4: Zinc salt, indium salt, sulfur source and nickel salt are dissolved in water-ethanol mixed solvent and subjected to hydrothermal reaction to obtain Ni-doped ZnIn2S4. Step S4, electrode preparation: Au NPs / g-C3N4 composite material dispersion is coated onto the first conductive substrate and annealed to obtain the photoanode; Ni-doped ZnIn2S4 dispersion is coated onto the second conductive substrate and dried to obtain the photocathode; Step S5, aptamer fixation: A solution of thiol-modified dimethoate aptamer is dropped onto the surface of the photoanode and incubated to fix the aptamer through Au-S bonds, thereby obtaining an aptamer-modified photoanode, which together with the photocathode constitutes the sensor.

[0009] In one optional embodiment, in step S1, the calcination conditions are: heating to 550°C at a rate of 2°C / min and holding at that temperature for 4 hours. In step S2, the amount of tubular g-C3N4 used is 0.8 g, and the volume fraction of methanol in the methanol-water solution is 20 wt.%. The chloroauric acid solution has a mass concentration of 1 wt.% and is added in an amount of 600 μL. The time for adsorption by stirring in the dark is 60 minutes, and the time for reduction by light is 60 minutes.

[0010] In one optional embodiment, in step S3, the nickel salt is NiCl2·6H2O, and its amount is 0.5% to 2% based on the molar ratio of Ni to Zn. The hydrothermal reaction temperature is 180°C, and the reaction time is 24 hours.

[0011] In one optional embodiment, in step S4, the concentration of Au NPs / g-C3N4 dispersion is 10 mg / mL, and the annealing temperature is 200°C; the concentration of Ni-doped ZnIn2S4 dispersion is 5 mg / mL, and the drying temperature is 180°C.

[0012] In one optional embodiment, in step S5, the concentration of the oxymethol aptamer solution is 4 μM, and the incubation conditions are: first incubation at 4°C for 1 h, and then incubation at room temperature for 1 h.

[0013] Thirdly, this disclosure also provides an application of a self-powered dual-photoelectrode photoelectrochemical sensor in the detection of omethoate.

[0014] Fourthly, this disclosure also provides a method for detecting omethoate using the self-powered dual-photoelectrode photoelectrochemical sensor described above, comprising the following steps: Step A1: The photoanode and photocathode are placed in the anolyte and catholyte, respectively, and the anode and cathode chambers are separated by a proton exchange membrane; Step A2: Add the sample to be tested to the anolyte and record the photocurrent signal under visible light irradiation; Step A3: Based on the linear relationship between the photocurrent response value and the logarithm of the omethoate concentration, quantitative detection of omethoate is achieved.

[0015] In one optional embodiment, the anolyte is a phosphate buffer solution, and the catholyte is a sodium sulfate solution containing ascorbic acid; The linear detection range of the omethoate concentration is 0.001–1000 ng / mL, and the detection limit is 2.75 pM.

[0016] The beneficial effects of this invention are: 1. A dual-photoelectrode self-powered system was constructed. The built-in electric field is formed by the Fermi level difference between the Au NPs / g-C3N4 photoanode and the Ni-doped ZnIn2S4 photocathode. Self-powered detection can be achieved without external bias voltage, which simplifies the device and reduces interference. 2. The photoanode uses tubular g-C3N4 to enhance light capture, loads Au nanoparticles to broaden visible light absorption, and stabilizes the thiol aptamer through Au-S bonds to achieve specific recognition of omethoate; 3. Ni doping in the photocathode modulates the local electronic structure of ZnIn2S4. Ni substitution of Zn sites shifts the binding energies of Zn 2p and S 2p, shifts the conduction band level upward, enhances electron reduction capability, and the network nanosheet structure increases the interface area, promoting electron utilization.

[0017] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention are realized and obtained in accordance with the structures particularly pointed out in the description, claims and drawings.

[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description

[0019] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0020] Figure 1 This is a morphology characterization image of Au NPs / g-C3N4 and Ni-doped ZnIn2S4 provided in an embodiment of this disclosure. Figure 1 A is the first SEM image of g-C3N4. Figure 2 B is the second SEM image of g-C3N4. Figure 2 C is a TEM image of Au NPs / g-C3N4. Figure 2 D is the distribution diagram of the second element in Au NPs / g-C3N4. Figure 2 E is the distribution diagram of the second element in Au NPs / g-C3N4. Figure 2 F is a SEM image of Ni-doped ZnIn2S4. Figure 2 G is a TEM image of Ni-doped ZnIn2S4. Figure 2 H is an HRTEM image of Ni-doped ZnIn2S4. Figure 2 I is the first elemental distribution diagram of Ni-doped ZnIn2S4. Figure 2 J is the second elemental distribution diagram of Ni-doped ZnIn2S4; Figure 2 The X-ray diffraction pattern, ultraviolet-visible diffuse reflectance spectrum, and band gap diagram of a material provided in this embodiment of the disclosure are as follows: Figure 2 A shows the XRD patterns of g-C3N4 and Au NPs / g-C3N4. Figure 2 B represents the XRD patterns of ZnIn2S4 and Ni-doped ZnIn2S4. Figure 2 C represents the UV-vis DRS plot of g-C3N4 / Au NPs / g-C3N4. Figure 2D is the UV-vis DRS plot of ZnIn2S4 / Ni-doped ZnIn2S4. Figure 2 E is the bandgap calculation diagram. Figure 2 F represents the VB-XPS valence band spectrum; Figure 3 The photocurrent response curve and electrochemical impedance spectroscopy of a material provided in this embodiment of the present disclosure are as follows: Figure 3 A represents the It curves of Au NPs / g-C3N4 under different amounts of chloroauric acid added. Figure 3 B represents the It curves of Ni-doped ZnIn2S4 with different Ni doping ratios. Figure 3 C represents the photocurrent comparison of the optimal material. Figure 3 D is the EIS diagram of the photoanode. Figure 3 E is the EIS diagram of the photocathode. Figure 3 F represents the change in photocurrent before and after aptamer modification and binding with omethoate. Figure 4 This is an analytical performance graph of a sensor provided in an embodiment of the present disclosure. Figure 4 A shows the photocurrent response curves of different concentrations of dimethoate. Figure 4 B is the linear standard curve. Figure 4 C represents the operational stability curve. Figure 4 D is a selective histogram. Figure 4 E is a bar chart representing long-term stability. Figure 4 F is a reproducibility bar chart. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Studies have found that omethoate is a highly toxic organophosphate insecticide with strong systemic activity and a broad insecticidal spectrum, and is widely used in agricultural production. However, improper application can easily lead to omethoate residues in agricultural products, soil, and water bodies, which can migrate and accumulate through the food chain, inhibiting the activity of human acetylcholinesterase and posing potential harm to the nervous system. Therefore, establishing a rapid, sensitive, and reliable method for detecting omethoate residues is of great significance for ensuring food safety and the ecological environment.

[0023] In related technologies, the detection of omethoate mainly relies on instrumental analysis methods such as high-performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS). These methods are highly accurate, but the equipment is expensive, the pretreatment is complex, and they require professional personnel to operate, making it difficult to meet the needs of rapid on-site detection. Photoelectrochemical sensing technology has advantages such as low background noise and high sensitivity due to the separation of excitation light and detection electrical signals. However, traditional photoelectrochemical sensors often use a three-electrode system and require an external bias voltage, which increases system energy consumption and complexity, hindering portable applications.

[0024] The shortcomings of the above solutions are the result of the inventor's practical experience and careful research. Therefore, the discovery process of the above problems and the solutions proposed in this disclosure below should be considered as the inventor's contribution to this disclosure.

[0025] Based on the above research, this disclosure provides a self-powered dual-photoelectrode photoelectrochemical sensor, comprising: an AuNPs / g-C3N4 photoanode and a Ni-doped ZnIn2S4 photocathode; an oxydimethoate aptamer is fixed on the surface of the photoanode; the AuNPs / g-C3N4 is a composite material of tubular graphitic carbon nitride with gold nanoparticles loaded on the surface, and the Ni-doped ZnIn2S4 is nickel ion-doped indium zinc sulfide.

[0026] In at least one embodiment, the nucleotide sequence of the oxymethol aptamer is: 5′-Thiol-C6-AAGCTTTTTTGACTGACTGCAGCGATTCTTGATCGCCACGGTCTGGAAAAAGAG-3′.

[0027] This disclosure also provides a method for preparing a self-powered dual-photoelectrode photoelectrochemical sensor, applicable to the preparation of the self-powered dual-photoelectrode photoelectrochemical sensor as described above, comprising the following steps: Step S1, Preparation of tubular g-C3N4: Melamine is dissolved in ethylene glycol, and nitric acid aqueous solution is added to form a gel. After filtration, washing, and drying, the gel is calcined in an air atmosphere to obtain tubular g-C3N4. Step S2, preparation of Au NPs / g-C3N4: tubular g-C3N4 is dispersed in methanol-water solution, chloroauric acid solution is added, and after adsorption by stirring in the dark, gold nanoparticles are deposited by light reduction to obtain Au NPs / g-C3N4 composite material. Step S3, Preparation of Ni-doped ZnIn2S4: Zinc salt, indium salt, sulfur source and nickel salt are dissolved in water-ethanol mixed solvent and subjected to hydrothermal reaction to obtain Ni-doped ZnIn2S4. Step S4, electrode preparation: Au NPs / g-C3N4 composite material dispersion is coated onto the first conductive substrate and annealed to obtain the photoanode; Ni-doped ZnIn2S4 dispersion is coated onto the second conductive substrate and dried to obtain the photocathode; Step S5, aptamer fixation: A solution of thiol-modified dimethoate aptamer is dropped onto the surface of the photoanode and incubated to fix the aptamer through Au-S bonds, thereby obtaining an aptamer-modified photoanode, which together with the photocathode constitutes the sensor.

[0028] In at least one embodiment, step S1 specifically involves the following steps: dissolving 2 g of melamine in 60 mL of ethylene glycol and stirring magnetically to obtain a transparent solution. Preparing a solution by mixing 5 mL of nitric acid with 200 mL of deionized water, adding 45 mL of this solution to the mixture, and stirring continuously for 10 min to form a white gel. Filtering the gel through a 0.22 μm nylon membrane, washing the solid three times with ethanol, heating it to 550 °C at 2 °C / min in air and holding it at that temperature for 4 h, then cooling it to room temperature to obtain tubular g-C3N4. In at least one embodiment, step S2 specifically involves the following steps: 0.8 g of tubular g-C3N4 powder is dispersed in 80 mL of methanol-water solution (20 wt.% methanol by volume), ultrasonically dispersed for 10 min, and then magnetically stirred for 20 min. Under light-protected conditions, 600 μL of chloroauric acid solution with a mass concentration of 1 wt.% is added dropwise, and stirring is continued for 60 min in the dark to allow gold ions to be fully adsorbed onto the g-C3N4 surface. Subsequently, under continuous stirring, the surface is irradiated with a xenon lamp for 60 min to reduce the gold ions in situ to Au nanoparticles and deposit them on the g-C3N4 surface. The product is then centrifuged, washed several times with deionized water and ethanol, and dried at 60 °C for 8 h to obtain the Au NPs / g-C3N4 composite material.

[0029] In at least one embodiment, step S3 specifically involves the following steps: 0.12 mmol ZnSO4·7H2O, 0.24 mmol InCl3·4H2O, 0.48 mmol thioacetamide, and an appropriate amount of NiCl2·6H2O (controlling the molar ratio of Ni to Zn to be 1%) are dissolved in a mixed solvent of 15 mL deionized water and 15 mL anhydrous ethanol. The mixture is magnetically stirred for 30 min, and the precursor solution is transferred to a polytetrafluoroethylene-lined autoclave. The mixture is then hydrothermally reacted at 180 °C for 24 h. After natural cooling, the mixture is centrifuged, washed three times each with deionized water and anhydrous ethanol, and vacuum dried at 60 °C to obtain Ni-doped ZnIn2S4. Pure ZnIn2S4 prepared using the same steps without the addition of NiCl2·6H2O is used as a comparison.

[0030] In at least one embodiment, the specific operation steps of step S4 are as follows: electrode preparation, FTO conductive glass is ultrasonically cleaned in deionized water and ethanol for 30 min each, immersed in a mixed acid solution (H2O2:H2SO4, volume ratio 1:3) for 100 s, rinsed with ultrapure water, and dried for later use. Photoanode preparation: Au NPs / g-C3N4 composite material was dispersed in Nafion / ethanol (volume ratio 1:4) at a concentration of 10 mg / mL. After ultrasonic dispersion, 50 μL was dropped onto the FTO surface and annealed at 200 ℃ for 7 min to obtain AuNPs / g-C3N4 / FTO photoanode. Photocathode preparation: Ni-doped ZnIn2S4 was dispersed in an ethylene glycol / water (volume ratio 1:1) mixed solvent at a concentration of 5 mg / mL and ultrasonically dispersed until uniform. 50 μL was drop-coated onto the FTO surface and dried at 180 ℃ for 30 min to obtain the Ni-doped ZnIn2S4 / FTO photocathode.

[0031] In at least one embodiment, step S5 specifically involves the following steps: aptamer fixation. The nucleotide sequence of the oxymethol aptamer is: 5′-Thiol-C6-AAGCT TTTTT GACTG ACTGC AGCGA TTCTT GATCG CCACGGTCTG GAAAA AGAG-3′ (SEQ ID NO:1). The aptamer is prepared into a 4 μM solution using 0.01 M phosphate buffer (PBS) at pH 7.4. 20 μL of the aptamer solution is dropped onto the surface of the Au NPs / g-C3N4 / FTO photoanode. The solution is incubated at 4°C for 1 h, then at room temperature for 1 h. Unbound aptamers are removed by rinsing with PBS, thus obtaining the aptamer-modified photoanode, which, together with the Ni-doped ZnIn2S4 / FTO photocathode, constitutes the sensor.

[0032] Reference Figure 1 In at least one embodiment, the tubular g-C3N4 surface exhibits a porous structure. The tubular morphology is conducive to multiple reflections and scattering of light, enhancing light utilization efficiency. Au nanoparticles are uniformly deposited on the g-C3N4 surface in an irregular spherical shape. Ni-doped ZnIn2S4 consists of a three-dimensional network structure composed of rolled nanosheets. Ni doping does not change the basic morphology. HRTEM shows that the lattice spacing is about 0.292 nm, belonging to the (104) crystal plane. The elemental distribution diagram shows that Ni, Zn, In, and S are uniformly distributed, proving that Ni has been successfully doped into the ZnIn2S4 lattice.

[0033] In at least one embodiment, XPS analysis showed that characteristic peaks of C, N, and Au were clearly observed in the full spectrum of Au NPs / g-C3N4, and the Au 4f signal confirmed that gold existed in the metallic state. For Ni-doped ZnIn2S4, full-spectrum scanning confirmed the coexistence of Zn, In, S, and Ni. High-resolution spectroscopy showed that, compared to pure ZnIn2S4, the binding energies of Zn 2p3 / 2 and Zn 2p1 / 2 shifted to higher energies after Ni doping, while S 2p... 3 / 2 and S 2p 1 / 2 The binding energy of Ni also shows a similar shift trend, while the binding energy of In 3d remains essentially unchanged. This indicates that Ni doping mainly affects the local coordination environment around Zn-S, with Ni atoms tending to substitute Zn sites, causing a redistribution of the local electronic structure. This conclusion is consistent with subsequent DFT calculations.

[0034] Reference Figure 2 In at least one embodiment, Figure 2 XRD patterns of A and 2B show that Au NPs / g-C3N4 exhibits diffraction peaks at 38.4° and 44.3° corresponding to the Au(111) and (200) crystal planes, respectively; Ni-doped ZnIn2S4 maintains a hexagonal phase structure, but the diffraction peaks shift to higher angles, proving that Ni is incorporated into the lattice. UV-vis DRS ( Figure 2 C and D) indicate that after Au loading, the absorption edge of g-C3N4 redshifts from 455 nm to approximately 480 nm, and a characteristic LSPR shoulder peak appears near 550 nm; the light absorption ability of Ni-doped ZnIn2S4 is significantly enhanced. Figure 2 E and F calculate the band gap and valence band position, and find that the conduction band potentials of g-C3N4 and Ni-doped ZnIn2S4 are -0.95V and -1.41V (vs. NHE), respectively. Ni doping causes a negative shift in the conduction band, which is beneficial to enhance the electron reduction ability and increase the potential difference between the two electrodes, thereby improving the self-powered driving force.

[0035] Reference Figure 3 In at least one embodiment, Figure 3 A and B optimized the amount of chloroauric acid and the Ni doping ratio, determining that 600 μL of chloroauric acid and 1% Ni doping were the optimal conditions. Figure 3 As shown in Figure C, the photocurrent of Au NPs / g-C3N4 and Ni-doped ZnIn2S4 is significantly improved compared to their respective single materials. (EIS test results) Figure 3 (D, E) indicates that the interfacial charge transfer resistance of the composite material is significantly reduced. After aptamer fixation, the photoanode photocurrent decreases; when dimethoate specifically binds to the aptamer, the photocurrent significantly increases. Figure 3 (F) confirms that target recognition events can modulate interface charge transport, providing a basis for quantitative detection.

[0036] Based on the above description, this disclosure also provides an application of a self-powered dual-photoelectrode photoelectrochemical sensor in the detection of omethoate.

[0037] Furthermore, this disclosure also provides a method for detecting omethoate using the self-powered dual-photoelectrode photoelectrochemical sensor described above, comprising the following steps: Step A1: The photoanode and photocathode are placed in the anolyte and catholyte, respectively, and the anode and cathode chambers are separated by a proton exchange membrane; Step A2: Add the sample to be tested to the anolyte and record the photocurrent signal under visible light irradiation; Step A3: Based on the linear relationship between the photocurrent response value and the logarithm of the omethoate concentration, quantitative detection of omethoate is achieved.

[0038] In at least one embodiment, the anolyte is a phosphate buffer solution, and the catholyte is a sodium sulfate solution containing ascorbic acid; the linear detection range of the omethoate concentration is 0.001–1000 ng / mL, and the detection limit is 2.75 pM.

[0039] Under optimal conditions, standard solutions of omethoate at different concentrations were added to the anolyte (0.1 M PBS, pH 7.4), and the catholyte was a 0.1 M Na₂SO₄ solution containing 0.1 M ascorbic acid. The anode and cathode chambers were separated by a Nafion 117 membrane. Figure 4 As shown in Figure A, the photocurrent increases regularly with increasing concentration of dimethoate. Figure 4 B showed a good linear relationship between photocurrent intensity and the logarithm of concentration in the range of 0.001–1000 ng / mL, with the regression equation being I(nA) = 247.73 × lg(C / ng·mL). -1 ) + 1816.75, correlation coefficient R 2 = 0.998, detection limit is 2.75 pM (S / N=3).

[0040] Reference Figure 4 In at least one embodiment, Figure 4 As shown in Figure A, the photocurrent shows almost no attenuation under continuous switching illumination cycling, indicating excellent operational stability. Using 100 times the concentration of chlorpyrifos, methyl parathion, and malathion as interfering agents... Figure 4 As shown in D, the sensor only shows a significant response to omethoate, demonstrating excellent selectivity. Figure 4 As shown in Figure E, the photocurrent of the electrode remained at more than 90% of its initial value after 5 days. Figure 4 As shown in F, the relative standard deviation of the five parallel electrodes is 1.73%, indicating good reproducibility and long-term stability.

[0041] Actual sample testing example: The actual samples used were water samples from the Yangtze River (Zhenjiang section) and commercially available Chinese cabbage. The Chinese cabbage samples were chopped and juiced, the juice was transferred to centrifuge tubes, centrifuged at 12000 rpm for 15 min, and the supernatant was collected. This supernatant was filtered through a 0.22 μm microporous membrane, and the filtrate was diluted 10-fold with 0.1M PBS (pH 7.4) for later use. For the Yangtze River water samples, after centrifugation to remove suspended solids, the supernatant was filtered through a 0.22 μm membrane and then directly analyzed.

[0042] The spiked recovery method was used, with three parallel determinations at each of the three spiking levels. The results are shown in Table 1. The recovery rate of the sensor ranged from 95.14% to 105.61%, and the relative standard deviation (RSD) ranged from 1.17% to 4.59%, confirming that the sensor has excellent accuracy and reliability in complex matrices.

[0043] Table 1. Detection results of omethoate in actual samples In the several embodiments provided in this application, it should be understood that the disclosed systems, apparatuses, and methods can be implemented in other ways. The apparatus embodiments described above are merely illustrative. For example, the division of units is only a logical functional division, and in actual implementation, there may be other division methods. Furthermore, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Based on the above-described ideal embodiments of the present invention, and through the above description, those skilled in the art can make various changes and modifications without departing from the technical spirit of the disclosed embodiments. The technical scope of the embodiments of this disclosure is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, characterized in that, include: AuNPs / g-C3N4 photoanode and Ni-doped ZnIn2S4 photocathode; The surface of the photoanode is fixed with an oxymethol aptamer; The AuNPs / g-C3N4 is a composite material with gold nanoparticles loaded on the surface of tubular graphitic carbon nitride, and the Ni-doped ZnIn2S4 is nickel ion-doped zinc sulfide.

2. The self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor as described in claim 1, characterized in that, The nucleotide sequence of the oxymethol aptamer is: 5′-Thiol-C6-AAGCTTTTTTGACTGACTGCAGCGATTCTTGATCGCCACGGTCTGGAAAAAGAG-3′.

3. A method for preparing a self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor, characterized in that, The method for preparing the self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor as described in claim 1 includes the following steps: Step S1, Preparation of tubular g-C3N4: Melamine is dissolved in ethylene glycol, and nitric acid aqueous solution is added to form a gel. After filtration, washing, and drying, the gel is calcined in an air atmosphere to obtain tubular g-C3N4. Step S2, preparation of Au NPs / g-C3N4: tubular g-C3N4 is dispersed in methanol-water solution, chloroauric acid solution is added, and after adsorption by stirring in the dark, gold nanoparticles are deposited by light reduction to obtain Au NPs / g-C3N4 composite material. Step S3, Preparation of Ni-doped ZnIn2S4: Zinc salt, indium salt, sulfur source and nickel salt are dissolved in a water-ethanol mixed solvent and subjected to hydrothermal reaction to obtain Ni-doped ZnIn2S4. Step S4, electrode preparation: Au NPs / g-C3N4 composite material dispersion is coated onto the first conductive substrate and annealed to obtain the photoanode; Ni-doped ZnIn2S4 dispersion is coated onto the second conductive substrate and dried to obtain the photocathode; Step S5, aptamer fixation: A solution of thiol-modified dimethoate aptamer is dropped onto the surface of the photoanode and incubated to fix the aptamer through Au-S bonds, thereby obtaining an aptamer-modified photoanode, which together with the photocathode constitutes the sensor.

4. The preparation method according to claim 3, characterized in that, In step S1, the calcination conditions are as follows: the temperature is increased to 550℃ at a rate of 2℃ / min, and held for 4 hours. In step S2, the amount of tubular g-C3N4 used is 0.8 g, and the volume fraction of methanol in the methanol-water solution is 20 wt.%. The chloroauric acid solution has a mass concentration of 1 wt.% and is added in an amount of 600 μL. The time for adsorption by stirring in the dark is 60 minutes, and the time for reduction by light is 60 minutes.

5. The preparation method according to claim 3, characterized in that, In step S3, the nickel salt is NiCl2·6H2O, and its amount is 0.5% to 2% based on the molar ratio of Ni to Zn. The hydrothermal reaction temperature is 180℃ and the time is 24h.

6. The preparation method according to claim 3, characterized in that, In step S4, the concentration of Au NPs / g-C3N4 dispersion is 10 mg / mL, and the annealing temperature is 200℃; the concentration of Ni-doped ZnIn2S4 dispersion is 5 mg / mL, and the drying temperature is 180℃.

7. The preparation method according to claim 3, characterized in that, In step S5, the concentration of the oxymethol aptamer solution is 4 μM, and the incubation conditions are: first incubation at 4℃ for 1 h, and then incubation at room temperature for 1 h.

8. The application of the self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor according to claim 1 in the detection of omethoate.

9. A method for detecting dimethoate using the self-powered ZnIn2S4 / g-C3N4 dual-electrode photoelectrochemical sensor as described in claim 1, characterized in that, Includes the following steps: Step A1: The photoanode and photocathode are placed in the anolyte and catholyte, respectively, and the anode and cathode chambers are separated by a proton exchange membrane; Step A2: Add the sample to be tested to the anolyte and record the photocurrent signal under visible light irradiation; Step A3: Based on the linear relationship between the photocurrent response value and the logarithm of the omethoate concentration, quantitative detection of omethoate is achieved.

10. The method as described in claim 9, characterized in that, The anolyte is a phosphate buffer solution, and the catholyte is a sodium sulfate solution containing ascorbic acid. The linear detection range of the omethoate concentration is 0.001–1000 ng / mL, and the detection limit is 2.75 pM.